2016
DOI: 10.4103/2008-7802.193092
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nanoparticles containing iron on blood and inflammatory markers in comparison to ferrous sulfate in anemic rats

Abstract: Background:Ferrous sulfate is the most used supplement for treating anemia, but it can result in unfavorable side effects. Nowadays, nanotechnology is used as a way to increase bioavailability and decrease the side effects of drugs and nutrients. This study investigates the effects of nanoparticles containing iron on blood and inflammatory markers in comparison to ferrous sulfate in anemic rats.Methods:To induce the model of hemolytic anemia, 50 mg/kg bw phenylhydrazine was injected intraperitoneally in rats o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
6
10
1
Order By: Relevance
“…This can be interpreted based on adequate bioavailability of iron nanoparticles and its easy movement through the plasma membrane due to its nanoscale size. A similar trend of elevation in Hb content and RBC count was observed when anemic rats are treated with IONPs (18) . The authors also found that in rats receiving 0.4 mg of IONPs per day, both RBC count and Hb content were significantly higher compared with rats receiving 0.4 mg/day ferrous sulphate and further increasing the dose Fe-NPs to a double dose (0.8mg/day) caused no further increases as compared with the results of using a single dose IONPs.…”
Section: Hematological Parameterssupporting
confidence: 72%
See 1 more Smart Citation
“…This can be interpreted based on adequate bioavailability of iron nanoparticles and its easy movement through the plasma membrane due to its nanoscale size. A similar trend of elevation in Hb content and RBC count was observed when anemic rats are treated with IONPs (18) . The authors also found that in rats receiving 0.4 mg of IONPs per day, both RBC count and Hb content were significantly higher compared with rats receiving 0.4 mg/day ferrous sulphate and further increasing the dose Fe-NPs to a double dose (0.8mg/day) caused no further increases as compared with the results of using a single dose IONPs.…”
Section: Hematological Parameterssupporting
confidence: 72%
“…In addition, its effects have been studied at different levels of biological activities such as molecular, cellular, tissues and whole organismal. In some studies, it had been found that the same effect produced by a single dose of iron oxide NPs provided more bioavailability than using a double NPs dose (18) .…”
Section: Performance and Toxicitymentioning
confidence: 99%
“…Basing on the blood analyses, obtained results showed an increased iron bioavailability following oral, single dose of NPs with iron in anemic animals. In case of multiple doses of nanoparticles and ferrous sulfate, obtained results were similar [18]. Another study described obtained results of Fe-based nanomaterials as an alternative iron delivery agents on humans and a rodent model.…”
Section: Introductionmentioning
confidence: 65%
“…8, 9, and 10). Similar studies, concerning the bioavailability of iron from “nano” form, were mostly performed on anemic animals or examined following the iron depletion period [18, 19, 48], where our preliminary studies were carried out on healthy, normally maintained mice. Comparison of data presented in the current work with similar studies may be misleading because of differences in employed NPs e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly treated by oral administration of ferrous sulfate supplements, but only a small part is absorbed in the upper intestinal tract and the remaining reaches the low tract where reacts with hydrogen peroxide and superoxide producing free radicals and unfavourable effects. The reduction of the size of iron to the nanometric scale, increases its bioavailability and gastrointestinal absorption [ 80 ]. Further coating such as lipids [ 81 , 82 ], folic acid and chitosan [ 83 ] resulted to improve iron-based NPs stability and NPs inclusion in a bacteria, i.e.…”
Section: Nanoparticle-based Therapymentioning
confidence: 99%